Uji Fitokimia Dan Aktivitas Antibakteri Ekstrak Dan Fraksi Daun Suji (Dracaena angustifolia Roxb.) Pada Bakteri Staphylococcus aureus ATCC 25923 - suyono saputri, alip desi (Sam Ratulangi University, 2025)
Staphylococcus aureus is the bacteria that causes the most cases of infection in the world. Most infectious disease therapy in Indonesia uses antibiotics. Incorrect use of antibiotics can increase resistance. One of the plants that has the potential as an alternative treatment for infections is suji leaves. The purpose of this study was to determine the potential of suji leaf extract and fraction on antibacterial activity in Staphylococcus aureus ATCC 25923 bacteria. Samples were extracted using the maceration method with 70% ethanol solvent and then fractionated using n-hexane, ethyl acetate, and water solvents. Phytochemical tests were carried out to determine alkaloids, flavonoids, tannins, saponins, polyphenols, triterpenoids and steroids. Antibacterial activity tests of suji leaf extracts and fractions were carried out using the well method at concentrations of 5%, 10%, and 15% respectively with a negative control of 70% ethanol and a positive control of ciprofloxacin. Suji leaf extracts and fractions contain alkaloids, flavonoids, tannins, saponins, steroids, and polyphenols. The extract, n-hexane fraction, and ethyl acetate fraction of suji leaves have antibacterial activity against Staphylococcus aureus ATCC 25923 bacteria. The inhibitory activity against Staphylococcus aureus ATCC 25923 bacteria was greatest in the ethyl acetate fraction at a concentration of 15% with an average inhibition zone of 19.6 mm but was not equivalent to the inhibition of the positive control ciprofloxacin